The effect of short circuit fault in three-phase core-typed transformer - N. F. M. Yasid; A. A. Alawady; M. F. M. Yousof; M. A. Talib; M. S. Kamarudin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Different techniques for monitoring the transformer condition are continuously discussed. This is due to the fact that transformers are one of the most expensive components in the power system network. Not to mention the cost to fix any failure occurred in the transformer that have becoming more expensive nowadays. Frequency response analysis (FRA) is found to be the best method to monitor the transformer reliability. This paper presents a continuation of study presented in previous paper [1]. The study performed a laboratory test to show that the response of a normal winding phase A can be affected by short circuit fault which occurred at LV winding phase a, b, and c. To further investigate, current paper performed FRA measurement and applied fault on all phases. The same procedure is repeated on a distribution transformer to verify the findings. This is to examine the effect of fault at winding of other phases to the response of measured phase.